Implementing Godly Play in educational settings: a cautionary tale - Grajczonek, Jan (British journal of religious education, 2017)
At the heart of all curriculum decision-making is the learner. Contemporary early childhood education theory and practice emphasises young children’s agency and voice in their learning paying particular attention to valuing each child’s sociocultural contexts. As learners, children are considered capable and active participants rather than as deficit and passive recipients. How does the implementation of godly play in prior-to-school and school early years settings sit within a contemporary view of childhood? To what extent does this programme align with early childhood theory and practice? This paper seeks to evaluate the presence and place of godly play (which is not a curriculum and nor does it claim to be a curriculum) in the religiously affiliated early childhood education context in either prior-to-school or school settings. It is to be emphasised that this paper isnot evaluatingthe presence and place of godly play in the faith community of the local parish where all who participate are believers coming together to share that faith and to have that faith strengthened. However, its presence and place in formal educational settings outside of parish faith communities is questionable and requires closer critique.